Diagnosis and management of Duchenne muscular dystrophy, part 2: respiratory, cardiac, bone health, and orthopaedic management. Issue 4 (April 2018) - Birnkrant, David J; Bushby, Katharine; Bann, Carla M; Alman, Benjamin A; Apkon, Susan D; Blackwell, Angela; Case, Laura E; Cripe, Linda; Hadjiyannakis, Stasia; Olson, Aaron K; Sheehan, Daniel W; Bolen, Julie; et al.
Summary: A coordinated, multidisciplinary approach to care is essential for optimum management of the primary manifestations and secondary complications of Duchenne muscular dystrophy (DMD). Contemporary care has been shaped by the availability of more sensitive diagnostic techniques and the earlier use of therapeutic interventions, which have the potential to improve patients' duration and quality of life. In part 2 of this update of the DMD care considerations, we present the latest recommendations for respiratory, cardiac, bone health and osteoporosis, and orthopaedic and surgical management for boys and men with DMD. Additionally, we provide guidance on cardiac management for female carriers of a disease-causing mutation. The new care considerations acknowledge the effects of long-term glucocorticoid use on the natural history of DMD, and the need for care guidance across the lifespan as patients live longer. The management of DMD looks set to change substantially as new genetic and molecular therapies become available.